Serum Zinc Level at Term Pregnancy and Newborn Anthropometry - Irma Seriana; Yusrawati Yusrawati; Gustina Lubis (Indonesian Socety of Obstetrics and Gynecology, 2015)
Objective: To determine the relationship between serum zinc level at term pregnancy and newborn anthropometry. Methods: This study is an observational study with cross-sectional design. Serum zinc level at term pregnancy was measured and then anthropometric measurement was done to the newborn, including birth weight, birth length and head circumference at birth. The data were statistically analyzed using regression correlation test. Results: Mean serum zinc level at term pregnancy is 36.01 Î¼g/dl (SD=18.34 Î¼g/dl), the average birth weight is 3158 gr (SD=480.4 gr), the average birth length is 48.42 cm (SD=1.75 cm) and the average head circumference at birth is 33.13 cm (SD=1.14 cm). There was no statistically significant relationship between serum zinc levels at term pregnancy and birth weight (p-value=0.152). Meanwhile, there are statistically significant relationships between serum zinc level at term pregnancy with birth length and head circumference with pvalue 0.026 and 0.012, respectively. Conclusion: Serum zinc level at term pregnancy is correlated with birth length and head circumference, but is not correlated with birth weight. [Indones J Obstet Gynecol 2015; 3-4: 190-195] Keywords: birth length, birth weight, head circumference at birth, serum zinc level, term pregnancy